Database for accidents and incidents in the biodiesel industry - Calvo Olivares, Romina Daniela (2014)
The present paper describes the development of an accident and incident database for the Biodiesel Industry for the period 2003-November 2013. The work performed is related to the collection of data from different documental sources and the subsequent setting of a database containing general information about adverse events, its sequence, mitigation, causes, and human, environmental and material consequences occurred in biodiesel facilities during the last ten years. This database came to fill a gap existing in this field. Availability of these data will allow applying risk analysis tools, having a management tool to check organization performance, generating lessons learned to avoid accident recurrence and identifying those accidents more likely to occur. Data statistical analysis shows that the frequency of accidents in biodiesel plants has an increasing tendency, being fires and explosions the main type of accidents that occurred. Inmediate causes and consequences of the accidents have also been analized. Finally, some conclusion are drawn concerning the need of maintaining an update accidental and incidental database and improving biodiesel plants safety based on information obtained.